Mitigating heat stress in tomato by synergetic effect of trichoderma and organic manures - Banjade, Dhurba; Khanal, Dipak; Regmi, Pratima; Shrestha, Aman; Banjade, Nirajan; Dahal, Binod (Journal of Agriculture and Natural Resources, 2024)
Tomatoes (Solanum lycopersicum) are one of the world's most extensively farmed and economically important crops. Its high nutritional value and flexibility make it a household staple and an important crop for farmers. However, heat stress is a major hazard to tomato output. Temperatures above 30°C have a negative impact on tomato plants' physiological processes, such as germination, flowering, and fruit set, resulting in lower production and quality. With the growing frequency of heat stress caused by global warming, solving this issue is crucial to preserving tomato output. Heat stress has an impact on tomato development and yield by interrupting photosynthesis, reducing pollen viability, and increasing oxidative damage to plant cells. This stress causes decreased fruit set, reduced fruit size, and worse fruit quality. Organic agriculture provides a sustainable solution for mitigating the negative impacts of heat stress. The use of bio-fungicides such as Trichoderma and organic manures has been shown to effectively reduce the effects of heat stress on tomato plants. Trichoderma improves plant resilience by creating systemic resistance, releasing growth hormones, and increasing nutrient intake. Organic manures such as goat manure, poultry dung, and vermicompost improve soil structure, boost water retention, and supply important nutrients that help plants cope with stress. Reduced heat stress is critical for preserving tomato crop output and quality, particularly in the face of global climate change. Promoting the use of Trichoderma and organic manures in tomato growing not only decreases the impacts of heat stress, but also reduces the need for chemical fertilizers, enhancing soil health and protecting the environment. Adopting such sustainable approaches will assure food security and the long-term viability of tomato production.